Determinación de Escherichia COLI 0157:H7 en productos cárnicos de mercados de la ciudad de Encarnación (Journal on studies and research of academic knowledge, 2012)
Escherichia coli 0157:H7 is an emergent pathogen associated with food transmitted diseases. The objective of this work was to detect the microorganism in raw ground beef, random samples in supermarket, butcher shops, food pantries and municipal fair city of Encarnación, totaling 30 samples in the period from July to November 2011. These samples were processed in between EMB and MacConkey sorbitol for isolation. Lactose positive colonies were pricked in ATS for typing and serology. Was not isolated from E. coli 0157:H7 in samples of raw ground beef, however include the presence ofKlebsiella sp. (56%), Proteus sp. (27%), Enterobacter sp., (17%), Escherichia coli sp. (10%) (No E. coli 0157:H7), Citrobactersp (7%), Pseudomnas sp (7%).The identification of these microorganisms in large numbers can pose risks to consumer health, are associated  with poor cleanliness and hygiene of the equipment used in transport and/or slaughter of meat products, as well as the improper handling.
Keywords: Escherichia coli 0157:H7; meat products